2007
DOI: 10.1016/j.virol.2006.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity and RNA polymerase degradation following Hsp90 inhibition in a range of negative strand viruses

Abstract: We have analyzed the effectiveness of Hsp90 inhibitors in blocking the replication of negative-strand RNA viruses. In cells infected with the prototype negative strand virus vesicular stomatitis virus (VSV), inhibiting Hsp90 activity reduced viral replication in cells infected at both high and low multiplicities of infection. This inhibition was observed using two Hsp90 inhibitors geldanamycin and radicicol. Silencing of Hsp90 expression using siRNA also reduced viral replication. Hsp90 inhibition changed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(144 citation statements)
references
References 39 publications
9
135
0
Order By: Relevance
“…There was significant decrease in colony formation in MV-CEA/GA group as compared to either single-agent MV-CEA alone at comparable MOIs, or single-agent GA (30 nM) in both cell lines, indicating that combination treatment significantly increases the antitumor effect of MV-CEA virotherapy. The IC 50 for MD-MB231 cells and SK0V3.IP cells treated with MV-CEA/GA were MOIs of 0.20 and 0.34, respectively, whereas MV-CEA alone did not achieve an IC 50 in either cell line up to the MOIs tested.…”
Section: Mv-cea/ga Combination Treatment Increased Antitumor Effect Imentioning
confidence: 87%
See 1 more Smart Citation
“…There was significant decrease in colony formation in MV-CEA/GA group as compared to either single-agent MV-CEA alone at comparable MOIs, or single-agent GA (30 nM) in both cell lines, indicating that combination treatment significantly increases the antitumor effect of MV-CEA virotherapy. The IC 50 for MD-MB231 cells and SK0V3.IP cells treated with MV-CEA/GA were MOIs of 0.20 and 0.34, respectively, whereas MV-CEA alone did not achieve an IC 50 in either cell line up to the MOIs tested.…”
Section: Mv-cea/ga Combination Treatment Increased Antitumor Effect Imentioning
confidence: 87%
“…The latter has been associated with suppression of replication of RNA viruses such as HCV 49 and paramyxoviruses. 50 Heat shock protein inhibitor/measles virus combination treatment could have additional advantages, since HSP70 induction in the tumor environment by GA or other heat shock protein inhibitors has the potential to result in augmentation of antitumoral immune response. HSP70 induction has been shown to increase lysability of tumor cells by cytotoxic T lymphocytes, without interfering with MHC class I expression and antigen presentation.…”
Section: Combining Measles Virus With Heat Shock Protein Inhibitors Cmentioning
confidence: 99%
“…Hsp90 has been believed to facilitate viral protein folding and activity of non-structural proteins such as polymerase, protease and helicase as well as the structural proteins [3]. The polymerase of several viruses require Hsp90 for genome replication which include influenza virus A [12], herpes simplex virus [26], flock house virus [27] and vesicular stomatitis virus and treatment with Hsp90 inhibitors such as geldanamycin and 17-AAG lead to degradation of polymerase complexes [28,22].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown and treatment with an Hsp90 inhibitor have revealed that Hsp90 activity is important for the rapid growth of negative-strand RNA viruses (9). Furthermore, Hsp90 has been shown to be required for the activity of hepatitis B virus reverse transcriptase (21,22).…”
Section: Discussionmentioning
confidence: 99%